2013
DOI: 10.1007/s00439-013-1283-6
|View full text |Cite
|
Sign up to set email alerts
|

Confirming genes influencing risk to cleft lip with/without cleft palate in a case–parent trio study

Abstract: A collection of 1,108 case-parent trios ascertained through an isolated, non-syndromic cleft lip with or without cleft palate (CL/P) was used to replicate the findings from a genome-wide association study (GWAS) conducted by Beaty et al. (2010) where four different genes/regions were identified as influencing risk to CL/P. Tagging SNPs for 33 different genes were genotyped (1,269 SNPs). All four of the genes originally identified as showing genome-wide significance (IRF6, ABCA4 and MAF, plus the 8q24 region) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 26 publications
9
116
2
Order By: Relevance
“…Recent studies have reported association of nsCL/P with many loci throughout the genome [11][12][13][14][39][40][41][42] . Replication of those results on various populations and the investigation of mechanisms by which these variants influence cleft susceptibility are crucial for better understanding of genetic architecture of nsCL/P.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported association of nsCL/P with many loci throughout the genome [11][12][13][14][39][40][41][42] . Replication of those results on various populations and the investigation of mechanisms by which these variants influence cleft susceptibility are crucial for better understanding of genetic architecture of nsCL/P.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we focused on SNVs in 334 autosomal candidate genes for oral clefts (Jugessur et al 2009) plus 14 recently confirmed genes/regions yielding genome-wide significance in a meta-analysis (Ludwig et al 2012) and a replication study (Beaty et al 2013). Thus, 348 candidate genes were considered.…”
Section: Analyzing Called Variantsmentioning
confidence: 99%
“…Both genome-wide linkage and association studies have shown multiple genes influence risk to oral clefts (Mangold et al 2011;Marazita 2012) and recently at least a dozen different genes have been identified as genetic risk factors in genome-wide association studies (GWASs) (Ludwig et al 2012;Beaty et al 2013). Few of these genes, however, have causal variants identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although folic acid and smoking were found to influence OC outcomes, no significant interaction was demonstrated with the C677T variant. Beaty et al 20 found some evidence for geneenvironment interaction using available data on maternal smoking during pregnancy in European case-parent trios. The genes involved were GRID2 and ELAVL2.…”
Section: Environmental Factors and Geneenvironment Interactionmentioning
confidence: 99%